Rapid species identification and epidemiological analysis of carbapenem‐resistantAcinetobacterspp. by a PCR‐based open reading frame typing method. Issue 9 (September 2016) - Yamada, Yuki; Endo, Kentaro; Sawase, Kaori; Anetai, Marie; Narita, Kazuya; Hatakeyama, Yuji; Ishifuji, Katsunori; Kurota, Makiko; Suwabe, Akira
Abstract : N/A: The spread of carbapenem‐resistant Acinetobacter spp. has become a global problem. In this study, 18 carbapenem‐resistant Acinetobacter calcoaceticus‐baumannii (ACB) complexes, identified using a conventional biochemical method at our hospital during 2004‐2013, were studied for species identification and epidemiological analyses. Species identification was performed using matrix‐assisted laser desorption ionization‐time‐of‐flight MS, a partial sequence analysis of rpoB and a PCR‐based ORF typing (POT) method. The POT method can not only identify the species of ACB complexes but also simultaneously determine the international epidemic clones and the genetic identities of Acinetobacter baumannii in several hours. Carbapenem resistance gene detection by PCR, molecular epidemiological analysis by PFGE and Pasteur Institute multilocus sequence typing (MLST) analysis were performed. All three methods identified 18 isolates as A. baumannii ( n =10), Acinetobacter pittii ( n =4) and Acinetobacter nosocomialis ( n =4). A metallo‐ β ‐lactamase gene in all strains of A. pittii and A. nosocomialis and an IS Aba1 gene in the upstream of the bla OXA‐51‐like gene in eight strains of A. baumannii were detected, respectively, as carbapenemase‐related genes. Results from PFGE demonstrated that nine strains of A. baumannii were closely related genetically. Results of MLST analysis showed that A. baumannii are classifiable to sequence type 2. These results were consistent with those obtained using the POT method. This POT method can easily and rapidly identify the international epidemic clones and the identities of A. baumannii . It can be a useful tool for infection control.